Borehole heat exchanger with nanofluids as heat carrier. (March 2018) - Diglio, Giuseppe; Roselli, Carlo; Sasso, Maurizio; Jawali Channabasappa, Umavathi
Highlights: BoreHole Heat Exchanger with nanofluids as Heat carrier was numerically studied. A 1D mathematical model was tailored in order to account nanofluid physics properties. BoreHole Thermal Resistance was evaluated in the nanoparticles concentration range 0–1%. Cu-based nanofluid was characterized by higher BoreHole Thermal Resistance reduction. The cost of GSHP increases of 12% using Cu-based nanofluid with Cu concentration of 1%. Abstract: This paper presents numerical study on the use of nanofluids to replace conventional ethylene glycol/water mixture as heat carrier in a BoreHole Heat Exchanger. Nanofluids contain suspended metallic nanoparticles: increasing their concentration, in comparison to the base fluid, the thermal conductivity increases and the volumetric heat capacity decreases. The first effect is positive for the reduction of borehole thermal resistance, since it causes the grow of fluid convective heat transfer coefficient, while the second one is detrimental, due that it decreases the heat transfer between fluid and borehole wall. A numerical model based on energy and momentum balances is used to evaluate which is the best nanofluid with low nanoparticles volumetric concentration (0.1%–1%) that ensures the highest decreases of borehole thermal resistance and minimum increases of pressure drop among silver, copper, aluminium, alumina, copper oxide, graphite and silicon oxide. Moreover, a simple economic analysis was done. Results show that copper is characterized by highest borehole thermal resistance reduction, that reaches the value of about 3.8%, in comparison to that of base fluid, when nanoparticles volumetric concentration is 1%, but also the second one highest pressure drop. In this case, the cost of copper-based nanofluid is about 10 € m −1, i.e. about 12% of total cost of BoreHole Heat Exchange – Ground Source Heat Pump system.